What factors determine the value of an online teacher education experience from a teacher’s perspective? (2020)
E-learning is currently at the center of interest in the educational community, in a situation of global pandemics that forces us to reduce attendance in all aspects of our lives. Online courses have had a bad reputation due to the distance between the tutor and the apprentice and the high dropout rates. The main purpose is to analyze the evaluations made by teachers on di erent features of a course, by examining variables like content, technology, activities, final work, and format. The analysis covers the 50 online courses that form part of the continuous training o er of the Regional Ministry of Education of the Community of Madrid in courses 17–18 and 18–19 in which 7501 teachers have participated. The opinion of each participant is collected from a questionnaire at the end of the training activity. This has been validated by a group of experts from the Regional Centre for Innovation and Training, belonging to the Community of Madrid, using the Delphi method. To develop the methodology, a linear multivariate model was calculated on the independent variables and the dependent variable Net Promoter Score (NPS). Most of the findings are related to two central variables in the educational approaches that occur in digital scenarios. What the group of teachers’ values most is the content of the proposal, while the factor that they consider least important is the technology that supports the development of the course. The rest of the variables analyzed have little impact on the recommendation of the courses. Nevertheless, conclusions suggest that combining factors such as content, technology, and pedagogy are essential in experiences like these.